Caracterização da dinâmica folicular e controle farmacológico do ciclo estral de bovinos da raça pantaneira - Marinho, Walter Augusto dos Santos (2021)
The hypothesis of the present work is that Pantanal cattle, as they are taurine animals adapted to adverse environmental conditions, have distinct characteristics and particularities during the dynamics of follicular development. These reproductive peculiarities may be the answer to the low rates observed in the protocols for manipulation of the estrous cycle for the use of reproductive biotechnologies, such as fixed-time artificial insemination (FTAI). In the first chapter, the objective was to characterize the follicular dynamics, the wave pattern and its particularities for the Pantanal breed during follicular and luteal development. Eleven females of the Pantaneira breed were used with ultrasonographic evaluation of the ovaries every 24 hours during two consecutive estrous cycles. The pattern of follicular waves, interovulatory interval, number of recruited follicles, day of emergence of each wave, duration of each wave, growth rate, maximum follicular diameter and day of maximum diameter in each follicular wave were retrospectively evaluated. The follicular growth pattern showed cycles of 2 waves (2O) (15.78%) and 3 waves (3O) (84.21%). Interval between ovulation was similar (2O- 19.67±0.33; 3O - 19.56±0.30 days), duration of the first wave (5 days - 2O and 3O) and emergence of the 2nd wave in 2O and 3O cows (day 5.6±0.33 and 6±0.3, respectively). The duration of the ovulatory follicle (FO) in 2O (16±1.53 days) and for 3O (8.81±0.43 days). Growth rates in 3O cows (1st, 2nd and 3rd FD- 0.95±0.05; 0.87±0.06 and 1.01 ± 0.06 mm/day, respectively) versus cows with 2O (1st and 2nd FD - 0.75±0.003 and 0.66±0.067 mm/day, respectively). Luteolysis occurs on the same day (14 days), both in cows with 2O and 3O cycles. the Pantaneira cows showed similarities but the particularities were: the duration of the first wave was shorter and the earlier appearance of the second wave regardless of the pattern (2O and 3O) and third wave (3O), growth rates were lower and luteolysis was earlier with longer duration of the ovulatory follicle. In chapter 2, the objective was to characterize the ovarian follicular emergence and divergence of Pantanal females. Eleven cyclical Pantaneira bovine females were used. Ultrasonographic evaluation was performed every eight hours (8:00 am, 4:00 pm and 12:00 am) before ovulation up to 5 days after ovulation. There was an interval between the beginning of estrus and ovulation of 29.8 ± 1.7 hours; emergence of follicular emergence of 3.29 ± 1.542 h compared to D0; follicular deviation occurred 2.16 days after ovulation; dominant follicle (DF) growth rates 48 h before divergence 0.72 ± 0.092 mm/8h, subordinate FS follicle growth rates 0.14 ± 0.12 mm/8h; diameter of the FD at the beginning ofthe divergence of 8.10 ± 0.349 and of the FS 5.30 ± 0.376. In conclusion, the emergence of FD occurs right after ovulation, where the appearance of FS is later than FD. The DF has a larger diameter in relation to the FS since its emergence with higher growth rates until the follicular deviation. In Chapter 3, the objective was to evaluate the potential for synchronization of ovulation using two estradiol esters, benzoate and estradiol cypionate in Pantanal cows. Eleven pantaneira bovine females were used. On a random day of the estrous cycle, all animals received a single-dose intravaginal progesterone device (P4) and application of 2.0mg of estradiol benzoate intramuscularly (IM) on D0. On D8, the P4 device was removed and PGF2α IM was applied. The animals were divided into 3 groups: BE (1 mg-estradiol benzoate); EC (1mgEstradiol Cypionate) and Control (without ovulation inducer). The rate of animals that responded to the protocol was 73.3%, resulting in 81.81% of ovulations regardless of the group. For the BE treatment, the ovulation rate was 81.71%, CE was 88.88%. The FD size on D8 for all treatments was on average 9.72 mm. The largest diameter of the DF did not differ after implant removal for BE (11.09±0.48), CE (12.47±0.92). The pre-ovulatory follicle size for BE (10.7±0.64) and CE (11.98±0.95). It is concluded that the treatments with BE and EC were efficient in inducing ovulation in a synchronized way.